The relationship between syntactic knowledge and reading comprehension in EFL learners - Morvay, Gabriella (Studies in Second Language Learning and Teaching, 2012)
Via a variety of measurements, 64 Hungarian native speakers in the 12th grade learning English as a foreign language in Slovakia were tested in a cross-sectional correlational study in order to determine the relationship between the ability to process complex syntax and foreign language reading comprehension. The test instruments involved a standardized reading comprehension test in English, and a test of syntactic knowledge in both Hungarian and English, in addition to a background questionnaire in Hungarian. Power correlations and regression analyses rendered results that showed syntactic knowledge to be a statistically significant estimator for foreign language reading comprehension. The study provides evidence that the ability to process complex syntactic structures in a foreign language does contribute to one’s efficient reading comprehension in that language.